Broadband perfect Littrow diffraction metasurface under large-angle incidence - Zhu Jingyuan; Zhou Siliang; He Tao; Feng Chao; Wang Zhanshan; Dong Siyu; Cheng Xinbin (Nanophotonics)
Littrow diffraction devices are commonly used in the laser field (e.g., laser resonators and spectrometers), where system integration requires larger incidence angles and perfect broadband efficiency. Compared to traditional diffraction devices, which struggle to manipulate light paths under large-angle incidence, metasurfaces has the potential to enhance the broadband efficiency. Despite quasi three-dimensional metasurfaces effects, only perfect anomalous reflection under normal incidence at limited wavelengths was achieved due to energy flow mismatch in the broadband Littrow configuration. Here, we propose a supercell metasurface capable of regulating broadband non-local responses. The metasurface effectively suppresses non-local responses under Littrow mounting, while providing sufficient non-local responses through strong structural coupling effects when the incidence deviates from the Littrow mounting. A large-angle broadband Littrow diffraction metasurface in the mid-infrared spectrum (3.11 µm ∼ 3.52 µm) has been successfully realized, with 99 % efficiency at Littrow angle of 70°. Our results break through the bandwidth limitations of perfect diffraction, providing robust support for the practical applications of metasurfaces in Littrow diffraction devices.